Pulmonary cement embolization after vertebroplasty, an uncommon presentation of pulmonary embolism: A case report and literature review - Nishant Sinha (Lung India, 2015)
Pulmonary Cement Embolization (PCE) is a rare complication of vertebroplasty surgery. There is no clear guideline for management of this entity. There is no definite protocol for anticoagulation in PCE. This is a case report of our patient who was diagnosed to have Pulmonary Cement Embolization, which was quite significant involving both lungs. She was successfully managed without long term anticoagulation.